Comparison of the air layer near the surface at Mizuho Station with that at other sites in Antarctica - Ohata, Tetsuo; Wada, Makoto; Kawaguchi, Sadao (1982)
P(論文) The micrometeorological data obtained on a 30m tower at Mizuho Station in 1979 are analyzed and compared with the results of analysis of similar data obtained at various sites in Antarctica. Characteristics in the sloped katabatic wind area are obtained. The following statistical characteristics are derived for Mizuho Station. (1) Strong constancy of wind direction. (2) Strong wind speed. (3) Low percentage of the strong stable case in the 0-16m and 0-30m air layer. (4) In very stable cases, air temperature gradient between 16 and 30m increases more than in the 0-16m layer. (1) and (2) can be explained by the large slope inclination within the stations on the ice sheet. (3) is due to the vertical mixing by the strong wind. (4) seems to be related to the planetary boundary thickness which is said to become shallow in the case of a stable air layer on an inclined surface. departmental bulletin paper